Dynamic haematopoietic cell contribution to the developing and adult epicardium - Balmer, G; Bollini, S; Dubé, K; Martinez-Barbera, J; Williams, O; Riley, P (Springer Nature, 2014)
The epicardium is a cellular source with the potential to reconstitute lost cardiovascular tissue following myocardial infarction. Here we show that the adult epicardium contains a population of CD45+ haematopoietic cells (HCs), which are located proximal to coronary vessels and encased by extracellular matrix (ECM). This complex tertiary structure is established during the regenerative window between post-natal days 1 and 7. We show that these HCs proliferate within the first 24 h and are released between days 2 and 7 after myocardial infarction. The ECM subsequently reforms to encapsulate HCs after 21 days. Vav1-tdTomato labelling reveals an integral contribution of CD45+ HCs to the developing epicardium, which is not derived from the proepicardial organ. Transplantation experiments with either whole bone marrow or a Vav1+ subpopulation of cells confirm a contribution of HCs to the intact adult epicardium, which is elevated during the first 24 weeks of adult life but depleted in aged mice.